Short time between shifts and risk of injury among Danish hospital workers: a register-based cohort study - Nielsen, Helena B; Hansen, Åse M; Conway, Sadie H; Dyreborg, Johnny; Hansen, Johnni; Kolstad, Henrik A; Larsen, Ann D; Nabe-Nielsen, Kirsten; Pompeii, Lisa A; Garde, Anne H (Scandinavian journal of work, environment & health, 2019)
Objectives Short time between consecutive work shifts (quick returns, ie, ≤11 hours between shifts) is associated with sleepiness and fatigue, both of which have been linked to risk of injury. This paper aims to study quick returns between work shifts and risk of injury among Danish hospital workers. Method The study population included 69 200 employees, primarily working at hospitals, corresponding to 167 726 person years at risk between 2008-2015. Information on working hours was obtained from payroll data in the Danish Working Hour Database and linked, at an individual level, with data on 11 834 injury records identified in the National Patient Register and the Danish Register of Causes of Death. Multivariate Poisson regression models were used to calculate incidence rate ratios (IRR) with 95% confidence intervals (CI). Results Results showed the shorter the time between shifts, the higher the risk of injury. Thus, an elevated risk of injury was observed after quick returns compared with the standard 15-17 hours between shifts (IRR 1.39, 95% CI 1.23-1.58). Furthermore, when assessing the number of days since a quick return, the risk of injury was especially high within the first two days (day 1: IRR 1.39, 95% CI 1.23-1.58; day 2: IRR 1.39, 95% CI 1.21-1.58) following a quick return. Conclusions Our results suggest that quick returns increased the risk of injury, in particular within the first two days following a quick return. These findings point towards avoiding or reducing the number of quick returns in order to lower employees' risk of injury.